The Study of Creative Problem-Solving Thinking Skills Using Project-Based Learning Management Model with Community-Based Learning Resources for Grade 6 Students in The Subjects SOC 16101 Social Studies Religion and Culture at Bankanlueangdong School - Sukhampa, Netithorn; Tungkasamit, Tungkasamit (Journal for Developing the Social and Community, 2023)
The objectives of this research were 1) to study creative problem-solving skills of grade 6 students in the subject SOC 16101 Social Studies, Religion and Culture by using project-based learning management model with community-based learning by giving students average score of not less than 70% of the full score and the number of students who have passed the criteria 70 percent or more, 2) to study the learning achievement of grade 6 students in the subject SOC 16101 Social Studies, Religion and Culture by using a project-based learning management model with community-based learning by giving students average score of not less than 70% of the full score and the number of students who have passed the criteria of 70% or more and 3) to study the satisfaction of grade 6 students towards project-based learning management model with community-based learning resources. The target group used in this research were grade 6 students at Bankanlueangdong school who are studying in the second semester of the academic year 2021, of 18 students. The study was conducted by applying the one-shot case study design for data collection. Research instruments included 1) a learning management plan using project-based learning management model with community-based learning resources, 2) a creative problem-solving skill test, 3) an evaluation test and 4) a questionnaire for assessing student satisfaction towards project-based learning management model with community-based learning resources. Data were analyzed to find percentage, mean and standard deviation. The findings show that: 1) grade 6 students who received project-based learning management model with community-based learning resources scores on creative problem solving skills, the average was 59.78, representing 74.73% and there were 14 students who passed the criteria, representing 77.77% of the total number of students which is higher than the specified threshold, 2) grade 6 students who received project-based learning management model with community-based learning resources have an achievement score, the average was 21.61, representing 72.03%, and there were 14 students who passed the criteria, accounting for 77.77% of the total number of students which is higher than the specified threshold and 3) the satisfaction of grade 6 students towards project-based learning management model with community-based learning resources. Overall, the students had the highest level of satisfaction ( = 4.69, S.D. = 0.51). The students had the highest level of satisfaction in all aspects. They can be sorted as follows: Teachers ( = 4.83, S.D. = 0.37) Instructional Innovation Media ( = 4.79,S.D. = 0.39) Instructional Management ( = 4.71, S.D. = 0.46) Content (= 4.60, S.D. = 0.62) and evaluation measurement side ( = 4.51, S.D. = 0.69), respectively.